European principles of legal understanding and relevant governance in administrative court - Verbytskyi, Roman (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
Taking into account the tendencies of the development of judicial practice, special features of the application of the European principles of legal certainty and good governance in administrative legal proceedings are highlighted. A systematic interpretation was made and a conclusion was drawn about the general application of the aforementioned principles to protect the rights, freedoms and interests of individuals from violations by the subjects of power.